Design of W-type Index Chalcogenide Fiber for Highly Coherent Mid-IR Supercontinuum Generation - Rubén Sevilla (Journal of Lightwave Technology, 2018)
This paper presents the design of a W-type index chalcogenide fiber for mid-infrared beyond 10μm. The main advantages of the W-type index fiber are the possibility to control the chromatic dispersion with a larger possible core area for single-mode operation compared to a common step-index fiber and to enhance the fiber nonlinearity. Our fiber design consists of Ge15Sb15Se70 glass core, Ge20Se80 glass inner cladding and Ge20Sb5Se75 glass outer cladding. The optical mode distribution of the chalcogenide fiber is numerically calculated by employing edge-based finite elements. With 6-μm core diameter and 12-μm inner cladding diameter, the proposed fiber design exhibits flat anomalous dispersion in the wavelength range (4.3-6.5μm) with a peak of about 7ps/(nm.km). It also offers a high nonlinear coefficient of 0.12 W−1m−1 at a pump wavelength of 6.3 μm. The simulation results show that our proposed fiber design provides a highly coherent Mid-IR SC extending from 3.7 to 12 μm pumped at low peak pump power of 1kW.